A influência da expansão da Comunidade Católica Canção Nova no desenvolvimento de Cachoeira Paulista/SP e seus reflexos nos âmbitos social e econômico - Canuto, Romulo Augusto (2017)
The seek for a regional and economic development is a feature of all societies, crossing times and places. This reality becomes even more marked with the strenghtening of the multiple changes elapsed from the globalization process, with the fluidization of the political, social, economic and religious borders. It's in these lines of thoughts that this work is inserted, having the purpose of understanding the impacts of the installation of the Catholic Community Canção Nova in this economic and social reality in the city of Cachoeira Paulista - São Paulo, Brazil. Im this way, it's asked: What are the real impacts caused by the implantation of the New Song headquarters in Cachoeira Paulista city? How is this impact made in the city economy or infrastructure? How does the community deal with this impact? What are the solutions to this? To answer these research questions it was adopted a methodology centered in the case study, through a bibliographic review and document analysis, investigated by the models of regional development suggested by Marshall (1920), Myrdal (1968; 1957) and Hischman (1958; 1961), etcetera, just as well by the assumptions of the interaction models man-environment. With this analysis, the hypothesis that the "initial chaos" generated by the installation of the mentioned religious community in the studied city promoted the economic and social development of the locality, was corroborated